Double cryoenergy application (freeze‐thaw‐freeze) at growing myocardium: Lesion volume and effects on coronary arteries late after energy application. Implications for efficacy and safety in pediatric patients. (11th June 2019) - Schneider, Heike E.; Stahl, Maja; Schillinger, Wolfgang; Müller, Matthias; Backhoff, David; Schill, Manfred; Groene, Nehle; Krause, Ulrich; Sigler, Matthias; Paul, Thomas
Abstract: Introduction: Cryoenergy is accepted as an alternative to radiofrequency ablation (RFA) in childen for ablation of supraventricular tachycardia substrates. Single cryoenergy application has been shown to be inferior to RFA. Double cryoenergy application has therefore been introduced into clinical practice, but experience concerning efficacy is limited. Coronary artery stenosis has been reported as serious complication after RFA for arrhythmia substrates but not after single cryoablation. The purpose of the study was to assess lesion volume (efficacy) and risk of coronary artery damage (safety), late, that is, 6 months, after double cryoenergy application in a piglet model. Methods: Two sequential cycles of cryoenergy were delivered at −75°C for 4 minutes at the atrioventricular groove in five piglets. Animals were restudied after 6 months by coronary angiography and intracoronary ultrasound (ICUS). Ablation lesions were examined histologically and lesion volume was determined by three‐dimensional morphometric analysis. Results: Cryolesion volume was 174.04 ± 67.18 mm 3 for atrial and 238.69 ± 112.1 mm 3 for ventricular lesions ( P > .05). Ventricular lesions, 4.06 ± 1.05 mm, were significantly deeper than atrial lesions, 3.58 ± 0.78 mm, ( P < .05). In two of the 29 lesions, cryoenergy induced minor coronary artery injury with mild medial and adventitial thickening as well as minimal intimal proliferation, which had neither been detected by coronary angiography nor by ICUS. Conclusion: Late after double cryoenergy application at growing myocardium, subclinical minor affection of the coronary artery wall could be detected with minimal intimal proliferation. As lifetime sequelae of this finding remains unknown, further studies are warranted to address safety of repeated cycles of cryoenergy application for tachycardia substrates in children.